UCNPs@Zn0.5Cd0.5S Core-Shell and Yolk-Shell Nanostructures: Selective Synthesis, Characterization, and Near-Infrared-Mediated Photocatalytic Reduction of Cr(VI). (13th September 2018) - Wang, Wan-Ni; Dong, Wang; Huang, Chen-Xi; Liu, Bo; Cheng, Sheng; Qian, Haisheng
Abstract : Constructing near-infrared-light-mediated core-shell nanostructures incorporating upconversion nanoparticles (UCNPs) and semiconductors is of great importance for potential applications in photocatalysis, nano-biomedical engineering, solar cell, etc. In this work, we have demonstrated a two-step solution process to synthesize UCNPs@Zn0.5 Cd0.5 S core-shell nanoparticles (CSN). Firstly, a layer of AA-Zn(Cd)[OH] 4− composites was coated on UCNPs to form UCNPs@AA-Zn(Cd)[OH] 4− composites, which has been converted to UCNPs@Zn0.5 Cd0.5 S CSN via sulfidation reaction process using thioacetamide (TAA) as the sulfur source. Moreover, the UCNPs@Zn0.5 Cd0.5 S yolk-shell nanoparticles (YSN) have been obtained from the UCNPs@Zn0.5 Cd0.5 S CSN after calcination at 400°C, which show significantly photocatalytic activity for reduction of Cr(VI) under near-infrared light. All these can be attributed to the enhanced crystallization degree, resulting in enhanced energy transfer efficiency and separation efficiency of the photogenerated electrons and holes. An alternative strategy is provided in this study for fabrication of UCNP/semiconductor composites for various applications.